On the Widder inversion method in problems of statistical mechanics - Soldatov, A.V.; Seke, J.; Bogolubov, N.N. (Condensed Matter Physics, 2000)
An alternative way of reconstructing a function from its Laplace transform using the Widder inversion method was shown to be useful in treating some problems of nonequilibrium statistical mechanics. As an example of a successful application of the method, a decay was investigated of the excited atomic state in a simple, but nonetheless physically relevant, model featuring a two-level atom interacting with a continuum of ﬁeld modes. Показано, що альтернативний спосіб відновлення функції за її образом Лапласа, відомий як метод оберненого перетворення Уіддера, може бути корисним при розв’язуванні деяких проблем нерівноважної статистичної механіки. Як приклад успішного застосування цього підходу розглянуто процес релаксації збудженого стану атома у простій, але фізично змістовній моделі, яка описує взаємодію дворівневого атома з полями в континуальній границі.